EFEKTIFITAS METODE SUGGESTOPEDIA DALAM MENINGKATKAN PEMAHAMAN ENGLISH VOCABULARY - Ni Nyoman Ari Ratnadi; I Made Ngurah Oka Mahardika (Padma Sari: Jurnal Ilmu Pendidikan, 2024)
The purpose of this study was to describe the used of the suggestopedia method in learning English and the effectiveness of the suggestopedia method in increasing understanding of English vocabulary at Stikes Buleleng Pharmacy Study Program. This type of research was descriptive quantitative and qualitative research with the type of classroom action research (CAR). The subjects and place of this research were 41 students in the first semester of the Pharmacy Study Program. In collecting data, researcher used observation techniques, documentation, and measurement of learning achievement tests. As for the analysis, researcher used descriptive qualitative analysis techniques. The results shows that (1) the suggestopedia method was well applied in learning English and this was shown by the results of student observations, that the enthusiasm and activeness of students were very high in participating in learning by using suggestopedia method. (2) Learning by using suggestopedia method in English subjects has been declared effective, this is indicated by the results of student observations and student learning outcomes that have reached the criteria determined in this study.